Economic Uncertainty, Disagreement, and Credit Markets - Buraschi, Andrea; Trojani, Fabio; Vedolin, Andrea (Management Science, 2014)
We study how the equilibrium risk sharing of agents with heterogeneous perceptions of aggregate consumption growth affects bond and stock returns. Although credit spreads and their volatilities increase with the degree of heterogeneity, the decreasing risk premium on moderately levered equity can produce a violation of basic capital structure no-arbitrage relations. Using bottom-up proxies of aggregate belief dispersion, we give empirical support to the model predictions and show that risk premia on corporate bond and stock returns are systematically explained by their exposures to aggregate disagreement shocks. This paper was accepted by Jerome Detemple, finance.